2013
DOI: 10.1002/adhm.201300076
|View full text |Cite
|
Sign up to set email alerts
|

A Fast pH‐Switchable and Self‐Healing Supramolecular Hydrogel Carrier for Guided, Local Catheter Injection in the Infarcted Myocardium

Abstract: Minimally invasive intervention strategies after myocardial infarction use state-of-the-art catheter systems that are able to combine mapping of the infarcted area with precise, local injection of drugs. To this end, catheter delivery of drugs that are not immediately pumped out of the heart is still challenging, and requires a carrier matrix that in the solution state can be injected through a long catheter, and instantaneously gelates at the site of injection. To address this unmet need, a pH-switchable supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(191 citation statements)
references
References 40 publications
3
188
0
Order By: Relevance
“…At four week follow up, treated animals showed areas of viable myocardium suggesting that more favourable myocardial remodelling may have occurred in these animals. (129) These Multimodal approaches show particular promise for myocardial regeneration.…”
Section: The Case For Combining Biological Therapiesmentioning
confidence: 99%
“…At four week follow up, treated animals showed areas of viable myocardium suggesting that more favourable myocardial remodelling may have occurred in these animals. (129) These Multimodal approaches show particular promise for myocardial regeneration.…”
Section: The Case For Combining Biological Therapiesmentioning
confidence: 99%
“…Basak et al [7] prepared hydrogels of poly(vinyl alcohol) by crosslinking with maleic acid; they found that the swelling of the hydrogels was highest in intestinal fluid (pH 7.5) and lowest in simulated gastric fluid (pH 1.2); hydrogels loaded with vitamin B12 and salicylic acid exhibited colon-specific drug release behavior with a higher drug release in intestinal fluid (pH 7.5) than that in simulated gastric fluid (pH 1.2). Bastings et al [8] reported a pH-switchable supramolecular hydrogel by using fourfold hydrogen-bonding supramolecular ureidopyrimidinone (UPy) units coupled with alkyl urea spacers to poly(ethylene glycol) (PEG) chains. These UPy-modified PEG hydrogels formed fibers in aqueous solution that could cross-link to form transient supramolecular networks, and these unique UPy-transient networks were pH-responsive, which enabled a sol-to-gel switch in a subtle pH range.…”
Section: Organic-materials-based Ph-responsive Drug-delivery Systemsmentioning
confidence: 99%
“…Liu et al employed Hbond and dipole-dipole interactions to enhance the mechanical strength and fatigue resistance of physical hydrogels 11,12 . Meijer et al fabricated tough supramolecular hydrogels cross-linked by the H-bonds between selfcomplementary UPy units 13,14 . Scherman et al demonstrated the fabrication of supramolecular cross-linked hydrogels by the host-guest interactions of cucurbit [n] uril complexes [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%